Didactic Aspects of Distance Learning in the Conditions of Pandemic and Martial Law - Galushko, Olena; Kovalenko-Marchenkova, Yevheniia; Chistyakov, Volodymyr G. (Dnipropetrovsk State University of Internal Affairs, Dnipro, Ukraine, 2022)
ENG: The article deals with the topical issues of improving the effectiveness of the educational process in higher educational institutions in the conditions of a pandemic and martial law. The evolution of distance learning is considered. Peculiarities of the remote form of education, which functions on the basis of modern psychological and pedagogical and information and communication technologies, have been studied. The peculiarities of the organization of the educational process in higher educational institutions in the context of the pandemic and martial law were analyzed, in particular didactic aspects of the educational process in conditions of danger and increased stress. Special attention is paid to the psychological state of students and ways of reducing stress and activating their attention on the educational process, taking into account the types of information perception (audio, visual, kinesthetic, digital). Ways to improve the distance learning process in the conditions of a pandemic and martial law are proposed.

UKR: Стаття присвячена актуальним питанням підвищення ефективності навчального процесу у вищих учбових закладах в умовах пандемії та воєнного стану. Розглянуто еволюцію дистанційного навчання. Досліджено особливості дистанційної форми навчання, яка функціонує на основі сучасних психолого-педагогічних та інформаційно-комунікаційних технологій. Проаналізовано особливості організації навчального процесу у вищих учбових закладах в умах пандемії та воєнного стану, зокрема дидактичні аспекти навчального процесу в умовах небезпеки та підвищеного стресу. Особливу увагу приділено психологічному стану студентів та шляхам зниження стресу та активізації їх уваги на навчальному процесі з урахуванням типів сприйняття інформації (аудіали, візуали, кінестетики, діджитали). Запропоновано шляхи удосконалення дистанційного навчального процесу в умовах пандемії та воєнного стану.
Дидактичні аспекти дистанційного навчання в умовах пандемії та воєнного стану
O. Galushko: ORCID 0000-0002-4578-5820; Ye. Kovalenko-Marchenkova: ORCID 0000-0001-7350-7740
Keywords: distance learning; pandemic; martial law; psychological state; anxiety; learning; audio; visual; kinesthetic; digital; дистанційне навчання; пандемія; воєнний стан; психологічний стан; тривожність; засвоєння знань; аудіали; візуали; кінестетики; діджитали; КМЧС